Identification of methylated metabolites of oat avenanthramides in human plasma using UHPLC QToF-MS. (3rd April 2018) - Walsh, Jason; Haddock, Jordan; Blumberg, Jeffrey B.; McKay, Diane L.; Wei, Xiaoyong; Dolnikowski, Gregory; Chen, C.-Y. Oliver
Abstract: Oat avenanthramides (AVAs) are a group of phenolic alkaloids, consisting of an anthranilic acid and a hydroxycinnamic acid linked by a pseudo-peptide bond. Bioavailability of AVA is poor in humans, suggesting transformations for rapid excretion. Thus, we aim to identify metabolites of AVA isomers in plasma of humans after consuming AVA-enriched oats. After lipid removal, AVA and their metabolites in plasma were extracted with ethyl acetate and analysed using an Agilent UHPLC-QToF-MS. Pharmacokinetics of AVA-O showed a bimodal distribution with Cmax 1 and 2 for AVA-O at 5.9 ± 5.2 and 7.9 ± 7.0 ng/mL and Tmax 1 and 2 at 1.7 ± 0.7 and 3.1 ± 1.2 h, respectively. Only the methyl-AVA-O showed a single Cmax at 14 ± 9.9 ng/mL AVA-O equivalents and a Tmax of 2.4 ± 2.7 h. This analysis is the first to identify methylated metabolites of AVAs and AVA aglycones in human blood after acute AVA consumption.